O17.3 Declining rates of cervical intraepithelial NEOPLASIA after introduction of the HPV vaccine in british columbia, canada. (14th July 2019) - Donken, Robine; Niekerk, Dirk Van; Hamm, Jeremy; Smith, Laurie; Sadarangani, Manish; Naus, Monika; Money, Deborah; Dobson, Simon; Miller, Dianne; Krajden, Mel; Lee, Marette; Mitchell-Foster, Sheona; et al.
Abstract : Background: In 2008 British Columbia (BC), Canada, implemented a voluntary school-based HPV vaccination program for girls, born 1994 or later, with an average uptake of 63%. Given the long time-lead between infection and malignant disease, effects on cancer incidence will take decades to assess. To evaluate the early impact of the HPV vaccine in BC, ecological trends in cervical intraepithelial neoplasia (CIN) rates were assessed in young women before and after the implementation of the HPV vaccination program. Methods: From the population-based cervical cancer screening program database in BC, information on all Pap smears and histopathological abnormalities, in calendar years 2004–2017 in women under age 28 were obtained. Rates of cervical intraepithelial neoplasia (CIN) were calculated as the number of cases divided by the number of cytology specimens for that period. Incidence rate ratios (IRR) comparing pre- and post-vaccination years, adjusted for age and screening year, were calculated by piece-wise Poisson regression analysis. We performed a sensitivity analysis including only women eligible for routine screening. Results: The total number of screens in the unvaccinated cohort was 1, 417, 512 and in the vaccinated cohort 73, 343. After the introduction of the HPV vaccination program in BC, a decrease in the incidence of CIN was observed in vaccine-eligible birth cohorts. The adjusted IRR for CIN1, 2 and 3 were respectively 0.60 (95%CI 0.53–0.67), 0.49 (95%CI 0.41–0.57) and 0.39 (95%CI 0.32–0.47). Sensitivity analysis confirmed these findings, also indicating a significant decline in CIN rates in birth cohorts eligible for the HPV vaccination program. Conclusion: This study illustrates the population impact of the provincial school-based HPV vaccination program, by an observed decline in rates of CIN since introduction of the program. Further evaluation of the population-based impact includes a linkage between vaccination and screening registry. Disclosure: No significant relationships.